Respuesta :

Answer:

7/6

Step-by-step explanation:

w^2 - 7/3 w + 49/36 = 0

It's perfect square

(w - 7/6)^2 = 0

w - 7/6 = 0

w = 7/6

gmany

Answer:

[tex]\large\boxed{w=\dfrac{7}{6}}[/tex]

Step-by-step explanation:

[tex]w^2-\dfrac{7}{3}w+\dfrac{49}{36}=0\qquad\text{multiply both sides by 36}\\\\36w^2-36\!\!\!\!\diagup^{12}\cdot\dfrac{7}{3\!\!\!\!\diagup_1}w+36\!\!\!\!\diagup^1\cdot\dfrac{49}{36\!\!\!\!\diagup_1}=0\\\\36w^2-84w+49=0\\\\36w^2-42w-42w+49=0\\\\6w(6w-7)-7(6w-7)=0\\\\(6w-7)(6w-7)=0\\\\(6w-7)^2=0\iff 6w-7=0\qquad\text{add 7 to both sides}\\\\6w=7\qquad\text{divide both sides by 6}\\\\\boxed{w=\dfrac{7}{6}}[/tex]